2003
DOI: 10.1016/s0012-1606(03)00039-3
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-releasing hormone (gnrh) cells arise from cranial neural crest and adenohypophyseal regions of the neural plate in the zebrafish, danio rerio

Abstract: The olfactory placodes generate the primary sensory neurons of the olfactory sensory system. Additionally, the olfactory placodes have been proposed to generate a class of neuroendocrine cells containing gonadotropin-releasing hormone (GnRH). GnRH is a multifunctional decapeptide essential for the development of secondary sex characteristics in vertebrates as well as a neuromodulator within the central nervous system. Here, we show that endocrine and neuromodulatory GnRH cells arise from two separate, nonolfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
145
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 65 publications
12
145
0
3
Order By: Relevance
“…Consistent with this hypothesis, we have found that in zebrafish GnRH3 cells of the terminal nerve and GnRH2 cells of the midbrain (Fig. 2B,C) have their origin in the cranial neural crest [53,57,60] whereas the GnRH cells of the hypothalamus arise from the region of the adenohypophyseal placode [54,56,57,60] (Fig. 2D).…”
Section: Gnrh Cellssupporting
confidence: 73%
See 2 more Smart Citations
“…Consistent with this hypothesis, we have found that in zebrafish GnRH3 cells of the terminal nerve and GnRH2 cells of the midbrain (Fig. 2B,C) have their origin in the cranial neural crest [53,57,60] whereas the GnRH cells of the hypothalamus arise from the region of the adenohypophyseal placode [54,56,57,60] (Fig. 2D).…”
Section: Gnrh Cellssupporting
confidence: 73%
“…Adenohypophyseal development was not greatly disrupted in kal1a MO injected fish, yet a hypothalamic marker was completely absent in many injected fish [22]. Our data suggest kal1a gene is involved in both endocrine GnRH neuron and hypothalamic development, suggesting the precursors of GnRH cells may lie in the anterior hypothalamus [22] rather than the adenohypophysis as we previously reported [60].…”
Section: Further Analysis Of Gnrh Cell Originsupporting
confidence: 69%
See 1 more Smart Citation
“…In Myotis myotis, this presumably takes place at about D27 and a CRL of 4 mm. In recent studies, Whitlock et al (2003Whitlock et al ( , 2004 (2004) investigated over 300 serially sectioned human embryos and clearly demonstrated nasal crest material in several Š těrba stage 4 specimens directly underneath the basement membrane of the olfactory placode. This material originates from the nasal plate at the neurosomatic junction, as does the neural crest, and contains LHRH precursor cells (Verney et al, 2002).…”
Section: Discussion Topography and Development Of Tnmentioning
confidence: 99%
“…Whether or not the gonadotropin-releasing hormone-immunoreactive (GnRH) neurons arise from the olfactory placode or neural crest, they are the main source of GnRH (Krey and Silverman, 1978;King et al, 1984;Schwanzel-Fukuda et al, 1985, 1988Caldani et al, 1987;, 1990Zheng et al, 1988;Jennes, 1989;Wray et al, 1989aWray et al, , 1989bDemski et al, 1990;Ronnekeiv and Resco, 1990;Oelschlä ger and Northcutt, 1992;Muske, 1993;Northcutt and Muske, 1994;Jastrow et al, 1998). Recently, it was demonstrated in zebrafish that all hypothalamic GnRH cells arise from the neural crest (Whitlock et al, 2003). Here, the neuroendocrine population originates from the adenohypophyseal region of the developing anterior neural plate, whereas their neuromodulatory neurons originate from the cranial neural crest.…”
mentioning
confidence: 99%